Opposing regulation of TNF responses by IFN-γ and a PGE2-cAMP axis that is apparent in rheumatoid and immune checkpoint inhibitor-induced arthritis human IL-1β+ macrophages - Upneet K Sokhi; Ruoxi Yuan; Bikash Mishra; Yurii Chinenov; Anvita Singaraju; Karmela K Chan; Anne Bass; Richard D Bell; Laura Donlin; Lionel B Ivashkiv (eLife)
IL-1β-expressing macrophages have been described in rheumatoid arthritis (RA), immune checkpoint inhibitor-induced inflammatory arthritis (ICI-arthritis), and pancreatic cancer and proposed to be pathogenic. IL-1β+ macrophages express genes cooperatively induced by PGE2 and TNF signaling, but mechanisms that induce these cells are not known. We used an integrated transcriptomic and epigenomic analysis in primary human monocytes to study PGE2-TNF crosstalk, and how it is regulated by IFN-γ, as occurs in RA synovial macrophages. We identified a TNF + PGE2 (TP) induced gene expression signature that is enriched in IL1β+ RA and ICI-arthritis monocytic subsets, and includes genes in pathogenic IL-1, Notch and neutrophil chemokine pathways. ICI-arthritis myeloid cells mapped primarily onto four previously defined RA synovial monocytic clusters, and TP genes were expressed in a manner suggestive of a new functional monocyte subset. TP signature genes are distinct from canonical inflammatory NF-κB target genes such as TNF, IL6 and IL12B and are activated by cooperation of PGE2-induced AP-1, CEBP and NR4A family transcription factors with TNF-induced NF-κB activity. Unexpectedly, IFN-γ suppressed induction of AP-1, CEBP and NR4A activity to ablate induction of IL-1, Notch and neutrophil chemokine genes, while promoting expression of distinct inflammatory genes such as TNF and T cell chemokines like CXCL10. The opposing cross-regulation of PGE2 and IFN signaling in vitro was reflected in vivo in mutually exclusive expression of TP and IFN signatures in different cell clusters in RA and ICI-arthritis monocytes. These results reveal the basis for synergistic induction of inflammatory genes by PGE2 and TNF, and a novel regulatory axis whereby IFN-γ and PGE2 oppose each other to determine the balance between two distinct TNF-induced inflammatory gene expression programs relevant for RA and ICI-arthritis.